Match running performance of elite soccer players: VO2max and players position influences - Metaxas, T. I. (The Journal of Strength and Conditioning Research, 2021)
The aims of this study were (a) to assess the relationship between laboratory-measured VO2max with total distance covered in a soccer match, (b) to assess the relationship between laboratory-measured VO2max with the distance covered at a different running intensity in a soccer match, (c) to quantify different intensity running in various playing positions, and (d) to determine the differences of running performance between halves. Analyzed match running performance of the Greek elite (n = 14) soccer players using a global positioning system within the second division professional league. No correlation was found between VO2max and match running performance at any velocity. The players covered greater distances in the first half at all speed levels except walking. In the first half, they covered a greater distance than in the second half (1,533 vs. 1,297 m, p < 0.001; 879 vs. 708 m, p < 0.001; 433 vs. 359 m, p < 001; 185 vs. 152 m, p < 0.01; 81.4 vs. 65.5 m, p < 0.001) when jogging, running, high-intensity running, fast running, sprint and total, respectively. Wide players covered greater distances at fast running (p < 0.001) and sprint zone than the players who played at the axon of the field (348 vs. 297 and 186 vs. 113 m, respectively). In addition, midfielders covered a greater distance at high-intensity running zone and at fast running zone than the defenders and forwards (1,768 vs. 1,372 m, p < 0.01 and 1,768 vs. 1,361 m, p < 0.01; 686 vs. 878 m, p < 0.01 and 709 vs. 878 m, p < 0.05, respectively). The results demonstrate that match running performance and the distance covered depends on the tactical role of each player in the team. These data provide valuable information for coaches regarding the running profile of the Greek elite soccer players that could be used to design a more effective training program.